2022
DOI: 10.1039/d1dt03528b
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the reactivity, stability and biological activity of halido (NHC)gold(i) complexes

Abstract: The significance of the halido ligand (Cl-, Br-, I-) in halido[3-ethyl-4-phenyl-5-(2-methoxypyridin-5-yl)-1-propyl-1,3-dihydro-2H-imidazol-2-ylidene]gold(I) complexes (2, 3, 4) in terms of ligand exchange reactions, including the ligand scrambling to the bis[3-ethyl-4-phenyl-5-(2-methoxypyridin-5-yl)-1-propyl-1,3-dihydro-2H-imidazol-2-ylidene]gold(I) complex (5)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…The coordination of 4-aminoquinoline CQ or AQ to gold(I) also has consequences for the mechanisms affecting thiol redox homeostasis, and it can be inferred by observing that [AuCQPQ]PF 6 (1) is more potent in inhibiting the enzymatic activity of flavoenzymes than [AuAQPQ]PF 6 (2). This supports the hypothesis that compound (1) is more prone to interact with flavoenzymes than compound (2); namely, [AuCQPQ]PF 6 (1) is liable to undergo a ligand exchange reaction [43,44] in the presence of flavoenzymes. While much work remains to be conducted to clearly define the gold(I) hybrids' effect on thiol redox homeostasis in parasite cells, we were intrigued to find that the metallic hybrids displayed selectivity for inhibiting Sec-TrxRs versus Cys-TrxR, indicating that the gold(I) compounds share some reactivity to interact with Sec-TrxR.…”
Section: Discussionmentioning
confidence: 53%
“…The coordination of 4-aminoquinoline CQ or AQ to gold(I) also has consequences for the mechanisms affecting thiol redox homeostasis, and it can be inferred by observing that [AuCQPQ]PF 6 (1) is more potent in inhibiting the enzymatic activity of flavoenzymes than [AuAQPQ]PF 6 (2). This supports the hypothesis that compound (1) is more prone to interact with flavoenzymes than compound (2); namely, [AuCQPQ]PF 6 (1) is liable to undergo a ligand exchange reaction [43,44] in the presence of flavoenzymes. While much work remains to be conducted to clearly define the gold(I) hybrids' effect on thiol redox homeostasis in parasite cells, we were intrigued to find that the metallic hybrids displayed selectivity for inhibiting Sec-TrxRs versus Cys-TrxR, indicating that the gold(I) compounds share some reactivity to interact with Sec-TrxR.…”
Section: Discussionmentioning
confidence: 53%
“…These results indicated that the bis-NHC–Au­(I) complex had an obvious superiority in stability. The high cytotoxicity of this type of complex may be related to this …”
Section: Resultsmentioning
confidence: 99%
“…64 The reactivity observed in aqueous solvent mixtures was perfectly in line with the results reported for gold( i ) complexes. 5–7,65…”
Section: Resultsmentioning
confidence: 99%
“…64 The reactivity observed in aqueous solvent mixtures was perfectly in line with the results reported for gold(I) complexes. [5][6][7]65 In summary, compounds Au1-Au3 are stable in aqueous solvent mixtures with the retention of the NHC fragment. The equilibrium between the neutral halo-and the cationic dicarbene forms is dependent on the halide and the presence of water.…”
Section: Dalton Transactions Papermentioning
confidence: 93%